The Existence of the External World According to John Locke - Mohammad Saket; Seyed Mohammad Hakkak (Pizhūhish/hā-yi Falsafī- Kalāmī, 2018)
Our belief in the reality of things and people that we encounter is the topic of a fundamental discussion in philosophy known as "the existence of the external world." The essential question is whether we have knowledge of the existence of the external world or not. One of the most important answers that have been given to this issue is John Locke's theory of belief in reality which has been discussed in this paper. According to Locke, we have sensory knowledge of the external material world but what he refers to as "sensory knowledge" is apparently inconsistent with the general definition of knowledge in his philosophy. After studying the approaches of contemporary philosophers, we will show that sensory knowledge is consistent with the definition of knowledge in John Locke's philosophy. We will also review the arguments for sensory knowledge of the external world and John Locke's answer to skepticism. Also discussed in this paper is Locke's view that the most certain knowledge of the external world is our knowledge of the existence of God as well as that according to him, we do not have knowledge of other minds or spiritual essences and our certainty in regards to their existence is through faith.